(untitled) (Ustozlar uchun, 2026)
This article analyzes conceptual metaphors and their cultural interpretation in English and Uzbek languages. The study examines the relationship between language, cognition, and culture through comparative analysis of metaphorical expressions. The research identifies both universal and culture-specific features of cognitive metaphors in the two languages.